THE STUDENTS’ STRATEGY FORMATION IN LEARNING GENRE BASED WRITING THROUGH BLENDED SYNCHRONOUS LEARNING - Testiana Deni Wijayatiningsih; Dwi Anggani Linggar Bharati; Abdurrachman Faridi; Sri Wuli Fitriati (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
In this COVID 19 pandemic situation, EFL learners and lecturers must adapt with the situation. They had to learn from home and implemented blended synchronous learning approach to continue teaching learning processes for almost one semester. However, this condition had an impact on genre-based writing courses that writing is a complex skill and requires stages in creating a coherent text. To understand the students’ autonomous learning in genre- based writing class, it is momentous to analyse students’ self-regulatory skills, one of the skills is strategy formation in genre-based writing course. This research has an objective to describe the students’ strategy formation in genre-based writing class through blended synchronous learning. It administered a descriptive quantitative research method by using strategy formation questionnaire Likert scale. The questions consisted 10 questions self-concept indicator. The results showed that more than 40 % they had a good strategy formation in writing genre. Whereas there were some problems in creating text , such as; they sometimes applied mind map or outline before writing, they seldom reviewed their text using plagiarism application, and they sometimes created the ending of the text by reviewing all the text. Therefore, it is practical to create the text by considering strategy formation of self-regulatory skills if the teaching learning process applies blended synchronous learning approach.